Computational Simulation and Analysis of Local Thermal Comfort and Indoor Air Quality in Space with Displacement Ventilation - Kanaan, Mohamad; Amine, Semaan; Gazo-Hanna, Eddie (Engineering, Technology & Applied Science Research, 2024)
Displacement ventilation has been known for its capacity to lower energy consumption and improve air quality, but it has major thermal comfort limitations. The aim of this paper is to optimize the DV supply conditions by using computational fluid dynamics modeling to achieve acceptable CO2 concentration in the breathing layer at minimum energy cost while preventing local discomfort due to draft and air temperature difference between ankles and head. The results revealed that up to 44% energy savings can be achieved if the selection of supply conditions is optimized. The model can be put into practice to give recommendations on displacement ventilation preliminary design.